2011
DOI: 10.1590/s0100-54052011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Influência da adubação nitrogenada, época de plantio e aerosporos sobre a severidade da mancha de grãos em arroz de terras altas

Abstract: A mancha de grãos (MG) ocupa o segundo lugar em importância econômica entre as doença s do a rroz. Foi estuda da a influ ência de níveis de adubação nitrogenada, época de plantio e concentração de esporos no ar sobre a severidade da doença no campo. A severidade de MG, na cultivar BRS Bonança, foi avaliada em duas épocas de plantio (30 /11/2006 e 2 1/12 /200 6) e cinco doses de a duba ção nitrogenada (0 , 3 0 , 6 0 , 1 2 0 e 2 4 0 k g de N.ha -1 ) u tiliza ndo o delinea mento experimental de blocos ao acaso em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
1
8
0
2
Order By: Relevance
“…The RGDP values found show that the disease is distributed throughout all rice-cropping regions of Corrientes province. Similar studies performed in different parts of Brazil have informed that RGDP has increased and that RGD has become an economically important disease due to the susceptibility of most of the cultivars used and to the fact that predominant pathogens vary according to the region and meteorological conditions of each campaign, even within each region (da Silva-Lobo et al, 2011;Malavolta et al, 2007;Soave et al, 1984).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The RGDP values found show that the disease is distributed throughout all rice-cropping regions of Corrientes province. Similar studies performed in different parts of Brazil have informed that RGDP has increased and that RGD has become an economically important disease due to the susceptibility of most of the cultivars used and to the fact that predominant pathogens vary according to the region and meteorological conditions of each campaign, even within each region (da Silva-Lobo et al, 2011;Malavolta et al, 2007;Soave et al, 1984).…”
Section: Discussionmentioning
confidence: 79%
“…More complex weather variables such as DPrecTRH and DWet1, which need relative humidity daily records (that are not always available in historical weather data) for their calculations, decreased slightly their correlations with RGDI. Several authors agree that high relative humidity subserve RGDI and disease severity (Baite et al, 2020;Chhabra & Vij, 2020;da Silva-Lobo et al, 2011), while others have found no correlation between relative humidity and RGDI (Rawte, 2007). Concerning precipitation, although it is widely mentioned as an influential factor, information regarding the amounts required to incentivize infection is scarce (Baite et al, 2020;dos Santos et al, 2009;Huang et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alrededor de 35 especies de hongos han sido identificados como agente causal del manchado del grano en arroz (Rivero et al, 2012). Especies de los géneros Alternaria, Curvularia, Fusarium y Pyricularia han sido identificados como patógenos potenciales en el cultivo de arroz (da Silva-Lobo et al, 2011). La pigmentación de grano contaminado es de color gris, marrón y negro (Figura 1), reduciendo el rendimiento alrededor de 19% y calidad de semilla (Baite et al, 2020;Rivero et al, 2012;Dirchwolf et al, 2018).…”
Section: Manchado De Grano De Arroz Causados Por Hongos Fitopatógenosunclassified
“…Existe dispersa información sobre la relación entre la tolerancia a patógenos y nutrición mineral en el cultivo de arroz. Los hongos Rhizoctonia (Schurt et al, 2015), Alternaria, Fusarium, Curvularia Pyricularia has sido demostrados como patógenos potenciales en el cultivo de arroz (da Silva-Lobo et al, 2011). El manuscrito discute la relación entre la nutrición mineral y la incidencia/severidad de hongos fitopatógenos potenciales que afectan al cultivo de arroz.…”
Section: Introductionunclassified